Pushing back against power: Political economy and agroecology - Nehring, Ryan; Gliessman, Steve (2025)
From modest roots, agroecology has begun to enter the mainstream as a viable and desirable alternative for transforming food systems. National and international agricultural research organizations have started developing agroecology research programs while global philanthropic funds have been established to support the implementation of agroecological principles. Given that many of these same organizations have been fundamental to agricultural industrialization – epitomized by the Green Revolution – does the entry of agroecology into the mainstream still promise to challenge business-as-usual?